ANALISIS PENYEBAB KEKERASAN DALAM RUMAH TANGGA DAN PERKEMBANGAN ANAK: PERSPEKTIF HAM - Latunussa, Semmy B.A.; Tamher, Samsul; Budiman, Eren Arif (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Domestic violence is a serious issue that can adversely affect the growth and development of children. This study aims to analyze the causes of domestic violence and its impact on child development from a human rights perspective. The research employs a mixed methods approach, combining qualitative methods and literature review. Secondary data were analyzed from various sources such as official reports, statistical data, and academic literature. The findings show that domestic violence significantly impacts the emotional, social, and psychological development of children. Children who experience or witness violence are at risk of trauma, fear, and low self-esteem. This study emphasizes the importance of the role of parents and caregivers in creating a safe and supportive environment for children, as well as the need for interventions and education to prevent domestic violence.